EVALUATION OF VOLUMETRIC MAINTENANCE AFTER SINGLE AND MULTIPLE DENTAL EXTRACTION USING LAMINATED TITTANIUM SHEET - : TITÂNIO SEAL®” - Rech Feldmann, Cristina; Nespolo Martins, Jessica; Shiniti Mizutani, Fabio; Lazzari Ciotti, Danilo; Alberton, Victoria; Beatriz Alberton, Simone (Health and Society, 2022)
The post-extraction border preservation is a fundamental procedure to the maintenance of alveolar volume prioritizing an aesthetical and functional improvement in the im- plant’s positioning. This thesis’s objective was to evaluate the titanium membrane (Sur- gitime Titânio Seal® – Bionnovation, Brasil) covered post extraction alveolar bone di- mensional alterations, while comparing areas to unitary and multiple exodontias. 20 pre and post-operation tomographical exams were evaluated, from areas where unitary den- tal extractions (G1) and multiple dental extractions (G2) occurred. In every case, using the Titanium Seal post extraction alveolar preservation treatment, with no alveolus fil- ling. Measurements were obtained from the central region of the axial and area sections previous to the proceadure at the most cervical zones of bone peaks, plus two more me- asurements from 2 and 4 mm under the first point. Following, those measurements were transfered from the previously obtained absolute refurbishment length. Measurements were taken from the new total border length – at the central virtually representative re- gion of the extracted dental element. In both groups, differences among baseline and 6 months in height: -0,95mm ±0,89 (G1) and -1,95mm ±1,04 (G2) and 2mm volume: -1,10mm ±0,48 (G1) and -2,48mm ±1,08 (G2) were statistically representative. In any cases, the 4mm volume presented differences. Statistically, the bone loss was higher in Group 2. The present study have shown that the titanium-laminated sheet was effective when it comes to post-extraction alveolar preservation, in both unitary and multiple ex- tractions.